Literatur Review: Faktor Risiko yang Behubungan dengan Terjadinya Perdarahan Post Partum - Chusnul Khotimah; Anis Pravitasari; Devitasari Yulistian; Ida Ristiani; Kartika Sari (Universitas Ngudi Waluyo, 2024)
The incidence of post partum hemorrhage at Dr. Soemarno Sosroatmodjo Tanjung Selor in 2023 as many as 146. If post partum bleeding is not treated it will cause maternal death. Post partum hemorrhage is an unexpected cause and is the fastest cause of maternal death in Indonesia. Post partum hemorrhage is a condition of blood loss of more than 500 ml after vaginal delivery or more than 1000 ml after cesarean delivery. Causes of postpartum hemorrhage include uterine atony, retained placenta, laceration of the birth canal, retained placenta and blood clotting disorders. Risk factors for post-partum hemorrhage include: age, parity, gestational age, delivery distance, excessive stretching of the uterus (macrosomia, gemelli and polyhydramnios), precipitate parturition, labor induction, history of cesarean section, ante-partum bleeding (placenta previa, placental abruption ), prolonged first and second stages of labor. Objective: This literature review aims to determine the risk factors for post partum hemorrhage. Method: using literature study according to the topic. Literature studies were obtained from various sources, including journals ranging from 2017-2024. Article sources from Proquest and Google Scholar. from several journals that have been reviewed, post partum bleeding is one of the complications whose incidence rate is still high. And there is a relationship between risk factors and the incidence of post partum hemorrhage. Abstrak Angka kejadian perdarahan post partum di Rumah Sakit dr. Soemarno Sosroatmodjo Tanjung Selor pada Tahun 2023 sebanyak 146. Apabila perdarahan post partum tidak diatasi akan menyebabkan kematian ibu. Perdarahan post partum merupakan penyabab tak terduga dan menjadi penyebab tercepat kematian ibu di Indonesia. Perdarahan post partum adalah keadaan kehilangan darah lebih dari 500 ml setelah persalinan pervaginam atau lebih dari 1000 ml setelah persalinan seksio secaria. Penyebab perdarahan postpartum meliputi atonia uteri, retensio plasenta, laserasi jalan lahir, sisa plasenta dan gangguan pembekuan darah. Faktor risiko terjadi perdarahan post partum antara lain : usia, paritas, umur kehamilan, jarak persalinan, peregangan uterus yang berlebihan (macrosomia, gemelli dan polihidramnion), partus presipitatus, induksi persalinan, riwayat seksio secaria, perdarahan antepartum (plasenta previa, solusio plasenta), persalinan kala I dan II yang memanjang. literature review ini bertujuan untuk mengetahui faktor risiko dari perdarahan post partum. Metode: menggunakan studi literature sesuai dengan topik. Studi literature didapat dari berbagai sumber diantaranya dari jurnal berkisar tahun 2017-2024. Sumber artikel dari proquest dan google scholar. dari beberapa jurnal yang telah ditelaah, perdarahan post partum merupakan salah satu komplikasi yang angka kejadiannya masih tinggi. Dan ada hubungan antara faktor risiko dengan kejadian perdarahan post partum.